Synthesis of Chitosan Derivatives and Their Inhibition Effects on Methane Hydrates - Yue Zhang; Zhi Li; Xiaodeng Yang; Tianduo Li (Energies, 2022)
In recent years, the study of natural polymer products such as methane hydrate inhibitors has attracted more and more attention in the scientific research field. In order to achieve environmentally friendly and economical methane hydrate inhibitors with high activity, four chitosan derivatives were successfully synthesized and their methane hydrate inhibition effects were compared with chitosan (CS) and carboxymethyl chitosan (CMCS). Under the conditions of 6 MPa, 1 °C and 400 rpm, the induction time of methane hydrate was prolonged by 7.3 times with the addition of 0.1 wt% CS. It was found that chitosan with high hydrophobicity could effectively prevent methane gas from entering the water solution and reduce the driving force of methane hydrates, resulting in the extension of hydrate induction time. The hydrate inhibition effect of CMCS could be improved by the introduction of hydroxypropyl-3-trimethylamine and N-2-hydroxypropyl-3-isooctyl ether groups based on the enhancement of the molecular hydrophobicity. At the same time, the introduction of the trimethyl quaternary ammonium group increased the ion content in the aqueous solution, which further inhibited the nucleation and growth of methane hydrates. This work is supposed to serve as an inspiration for the further research and development of green kinetic hydrate inhibitors with high-efficiency.